A scoping review on muscle cramps and spasms in upper motor neuron disorder–two sides of the same coin? - Therkildsen, Eva Rudjord; Kaster, Pernille; Nielsen, Jens Bo (Frontiers in Neurology, 2024)
Background - Muscle cramps are typically regarded as benign muscle overactivity in healthy individuals, whereas spasms are linked to spasticity resulting from central motor lesions. However, their striking similarities made us hypothesize that cramping is an under-recognized and potentially misidentified aspect of spasticity. Methods - A systematic search on spasms and cramps in patients with Upper Motor Neuron Disorder (spinal cord injury, cerebral palsy, traumatic brain injury, and stroke) was carried out in Embase/Medline, aiming to describe the definitions, characteristics, and measures of spasms and cramps that are used in the scientific literature. Results – The search identified 4,202 studies, of which 253 were reviewed: 217 studies documented only muscle spasms, 7 studies reported only cramps, and 29 encompassed both. Most studies (n=216) lacked explicit definitions for either term. One-half omitted any description and when present, the clinical resemblance was significant. Various methods quantified cramp/spasm frequency, with self-reports being the most common approach. Conclusion - Muscle cramps and spasms probably represent related symptoms with a shared pathophysiological component. When considering future treatment strategies, it is important to recognize that part of the patient's spasms may be attributed to cramps.